RETRACTED: CSF p-tau as a potential cognition impairment biomarker in ALS - Gong, Zhongying; Gao, Lina; Lu, Yi; Wang, Zhiyun (Frontiers in Neurology, 2022)
Background Cerebrospinal fluid (CSF) and serum tau (t-tau, p-tau) are potential biomarkers for neurodegeneration in Alzheimer disease (AD), but their role in amyotrophic lateral sclerosis (ALS) is unclear. Objectives The aim of our study was to evaluate CSF and serum p-tau and t-tau in patients with ALS and to analyze the correlation and clinical parameters between them. Methods CSF and serum samples were obtained from 90 patients with ALS, 48 other neurological disease (OND), and 20 with AM (ALS mimic, AM) diseases. The levels of p-tau and t-tau in the CSF and serum were assessed with an enzyme-linked immunosorbent assay, and disease progression parameters, including the duration, the ALSFRS-R score, disease progression rate (DPR), the upper motor neuron (UMN) score, the Mini-mental State Examination (MMSE) score, the Montreal Cognitive Assessment (MoCA) score, and the Edinburgh Cognitive and Behavioral ALS Screen (ECAS) results, were analyzed by registered neurologists. Statistical analyses were performed using Prism software. Results Compared with controls, patients with ALS displayed significantly lower levels of CSF p-tau and p-tau:t-tau ratio. The CSF p-tau level in patients with ALS and cognition impairment was higher than that in patients with ALS who did not have cognition impairment. CSF p-tau level was negatively correlated with MMSE, MoCA, and ECAS total score and the specific score of ECAS in patients with ALS and cognition impairment. Conclusions The CSF p-tau level and p-tau:t-tau ratio were lower in patients with ALS than patients with OND and AM. Results suggest that CSF p-tau may be used as an index of cognition impairment in patients with ALS.